Isolation of some bacteria from cockroaches Periplaneta americana L. and Blattella germanica L. from some hospitals at al-Nasiriyah city and study the sensitivity for some antibiotics - جبر, أماني شاكر (University of Thi-Qar Journal of Science, 2013)
Four hundred and two samples of Cockroaches of Periplaneta americana and Blattella germanica have been collected from some hospitals in Nasiriyah city. Forty-nine species of bacteria were isolated from cuticle layer and bowel of the cockroaches. The number of total isolates are 983, These species appeared predominantly in Hussein educational Hospital which appeared in 64.9%, Haboubi hospital by 25.6%, and finally the houses by 9.5%. As repeated eight bacterial species are Proteus mirabilis, Staphlococcus aureus, Klebsiella pneumoniae, Escherichia coli, Enterococcus faecalis, Salmonella.spp, Pseudomonas aeruginosa, Serratia marcescen by 9.26% ,6.6% ,6.51%, 6.31%, 6.1%, 6.1%, 5.8% ,5.5% respectively. When it is testing for antibiotic sensitivity using 19 type of antibiotics the result showed Gram negative bacteria multiple resistance to most antibiotics, especially VA (30mg), PY (30mg) ,CRO (30mg) ,S (10mg) ,AMC (30mg) by (94.9%, 86.2%, 81.5%, 76.5%, 75.5%) respectively, as well as Grampositive bacteria showed multiple resistance, especially to SMZ (30mg) ,CAZ (30mg) by (80.3%, 77%)also showed bacteria species isolated from cockroaches collected from the hospital more resistant toantibiotics from that were collected from houses.